Handbook of nuclear medicine and molecular imaging : principles and clinical applications - Kim, E. Edmund; Lee, Dong-Soo; Tateishi, Ukihide; Baum, Richard P., 1954- (World Scientific Publishing Co., Ltd., 2012)
This handbook will provide updated information on nuclear medicine and molecular imaging techniques as well as its clinical applications, including radionuclide therapy, to trainees and practitioners of nuclear medicine, radiology and general medicine. Updated information on nuclear medicine and molecular imaging are vitally important and useful to both trainees and existing practitioners. Imaging techniques and agents are advancing and changing so rapidly that concise and pertinent information are absolutely necessary and helpful. It is hoped that this handbook will help readers be better equ.